If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 7y = 51 Solving 9 + 7y = 51 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 7y = 51 + -9 Combine like terms: 9 + -9 = 0 0 + 7y = 51 + -9 7y = 51 + -9 Combine like terms: 51 + -9 = 42 7y = 42 Divide each side by '7'. y = 6 Simplifying y = 6
| 9e-4=78.8 | | 9(2x+4)+7x= | | 8x^4+2x=0 | | 22-43=4(x-1)-4 | | h=-16(t)(t-9) | | -3x^2+21x-30=0 | | 10x^2-33xy+20y^2=0 | | 6h+2l=13 | | (4x+12)+6x= | | 2(y-3)=3y-5-y | | -2(a+5)=-26 | | 5(x+12)=27 | | -2x^2+14x-24=0 | | 4(2c+60)-2c=90 | | (2x+13)+8= | | 13=2b+3 | | 2y^2+y+10=0 | | 4(5x+4)= | | 8y-9=63 | | (3x+10)+(6x+8)=180 | | -9=r^4 | | 7(2x-6)= | | -2=-4y(-7y+1)+5(8+2y) | | 2x+x+2x+x= | | 2/3*9= | | 5+8n=8n-3 | | (m-3)-[n+6-(2m-5n+10)]+2= | | 18w+30z= | | 5px(-6)=150 | | 10t-4t+3t=8 | | x^2=-11x-24 | | 5-6p=n |